1979
DOI: 10.1021/bi00572a012
|View full text |Cite
|
Sign up to set email alerts
|

Molecular weight of (sodium(1+), potassium(1+) ion)-stimulated ATPase from shark rectal gland

Abstract: The (Na+,k+)ATPase from the rectal gland of Carcharhinus obscurus has been solubilized in Lubrol WX as an active complex containing 379,900 g of protein and 61 mol of phospholipid. This detergent-lipid-protein complex contains two catalytic subunits of molecular weight 106,400 and four glycopeptide subunits of protein molecular weight 36,600. The latter subunit has a total molecular weight of 51,700 when the carbohydrate is included. Attempts to dissociate this active enzyme complex to smaller size by increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Boyer's mechanism for A TP processing in F of b discussed earlier, is an example of such a need. In the case of the Na,+K + pump, support fo r a dimeric functional unit is perhaps indicated by attempts to solubilize the protein in benign detergents with retention of ATPase activity; active preparations obtained so far are in a dimeric state (190,191). The alternating access model in its simplest form would require ApK.…”
Section: Monomer or Oligomermentioning
confidence: 99%
“…Boyer's mechanism for A TP processing in F of b discussed earlier, is an example of such a need. In the case of the Na,+K + pump, support fo r a dimeric functional unit is perhaps indicated by attempts to solubilize the protein in benign detergents with retention of ATPase activity; active preparations obtained so far are in a dimeric state (190,191). The alternating access model in its simplest form would require ApK.…”
Section: Monomer or Oligomermentioning
confidence: 99%
“…Only about 90, however, are needed for proper functioning. Purified enzyme from S. acanthias or Carcharhinus obscurus has about 60 moles of phospholipid bound to each 300,000 g protein (48,67).…”
Section: Lipid Interactionsmentioning
confidence: 99%
“…The quaternary structure of Na + /K + ‐ATPase has been studied by solubilizing the membrane‐bound enzyme, purified from mammalian kidneys, with nonionic surfactants such as C 12 E 8 and Lubrol 1–6 . These studies have shown consistently that the two polypeptides, α and β, are noncovalently combined in a minimum structural unit, an αβ‐protomer.…”
mentioning
confidence: 99%